Review on condition monitoring techniques for water pipelines. (April 2022) - Latif, Jawwad; Shakir, Muhammad Zeeshan; Edwards, Neil; Jaszczykowski, Marcin; Ramzan, Naeem; Edwards, Victoria
Abstract: Condition monitoring in the water distribution network and sewerage pipelines is one of the primary concerns for water utility companies. The impact of complex interconnected parameters on pipe deterioration mechanisms, lengthy water transmission networks and resource utilisation makes maintenance procedure more challenging. Various condition monitoring techniques for underground water pipes are in practice by water utility companies. High resolution cameras, electromagnetic waves, laser radiation, ultrasonic waves, acoustic sensors, eddy current and thermal profiling methods are used for condition assessment. However, these technologies also have limitations depending on pipe material, size of pipe, types of defects, environmental factors, size of pipe network, water pressure and flow rates. The current review includes a wide range of condition monitoring techniques for water pipelines and also highlights key features and limitations of emerging techniques.